Epsilon-polylysine modified TiO2 (at) Au Jauns core-half shell structure nano material and preparation method and application thereof
By forming the Jauns core-half-shell structure of TiO2@Au with ε-polylysine modified TiO2@Au on TiO2 nanometer microspheres, the problem of low ROS generation efficiency under ultrasound was solved, and more efficient antibacterial effects were achieved. Lower ultrasonic power requirements.
Patent Information
- Application Number
- CN202411509217.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing TiO2 nanomaterials have fast recombination speed under ultrasonic radiation, resulting in low ROS generation efficiency and difficulty in effectively antibacterial.
Jauns core-half-shell structure nanomaterial modified with ε-polylysine, formed a semi-gold shell by plating on TiO2 nanometer microspheres, inhibiting electron-hole pair recombination, and passing ε-polylysine Targeted modification of acid improves antibacterial effects.
It improves the production rate of ROS under ultrasound, enhances the antibacterial ability, overcomes the problem of insufficient light penetration in photodynamic therapy, and achieves more effective antibacterial effects at lower ultrasound power.
Smart Images

Figure CN119386178A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a TiO2@Au Jauns core-semi-shell structure nanomaterial modified by ε-polylysine with sonodynamic antibacterial function and a preparation method and application thereof, belonging to the technical field of biomedical inorganic nanomaterials. Background Art
[0002] Photodynamic therapy (PDT) is a non-invasive treatment technique for superficial cancers such as skin cancer. The use of ROS produced by PDT to fight bacteria is currently a widely recognized antibacterial strategy. However, due to the limited penetration depth of light into human tissue, even near infrared (NIR) lasers can only penetrate a few millimeters of tissue, and the therapeutic effect of PDT in vivo is not ideal. In order to overcome the shortcomings of photodynamic therapy, sonodynamic therapy (SDT) with low-intensity ultrasound combined with sonosensitizers has been developed and has become a very promising cancer treatment method.
[0003] Studies have shown that under the action of ultrasonic radiation, TiO2 will cause electrons to transfer from the valence band to the conduction band, thereby forming electron-hole pairs in the valence band, which can oxidize water, O2, etc. to form ROS. However, the speed of TiO2 electron-hole pair recombination is relatively fast, resulting in low ROS generation efficiency. Therefore, it is necessary to develop materials that inhibit the speed of TiO2 electron-hole pair recombination. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a TiO2 nano-microsphere core, an outer layer covered with an Au half-shell, and a surface of an ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial having two different components, TiO2 and Au; the second purpose of the present invention is to provide a method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial; the third purpose of the present invention is to provide the application of the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial in antibacterial applications.
[0005] Technical solution: The present invention discloses a Jauns core-half shell structure nanomaterial of TiO2@Au modified with ε-polylysine. The Jauns core-half shell structure nanomaterial of TiO2@Au modified with ε-polylysine is a TiO2 nanosphere core coated with a gold atomic layer, on which a half gold shell is grown, and the outside is modified with ε-polylysine.
[0006] The present invention uses an ion sputtering apparatus to plate a layer of Au on the top of the TiO2 nano-microspheres, so that about half of the upper surface of the TiO2 nano-microspheres is plated with a layer of gold atoms, and a layer of half gold shell is reduced and grown on the gold atomic layer by sodium ascorbate (AA) in a HAuCl5 aqueous solution, and then modified with ε-polylysine. Among them, the TiO2 part of the Jauns core-semi-shell structure nanomaterial of the ε-polylysine-modified TiO2@Au can destroy the electron transport chain on the bacterial cell membrane under the action of ultrasound, and produce reactive oxygen (ROS) with antibacterial properties in the bacterial cells. The half-gold shell part of the Jauns core-semi-shell structure nanomaterial of the ε-polylysine-modified TiO2@Au can produce gas that drives the movement of the nanomaterial under the action of ultrasound. The ε-polylysine of the Jauns core-semi-shell structure nanomaterial of the ε-polylysine-modified TiO2@Au has the function of actively targeting the bacterial cell membrane.
[0007] A method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial of the present invention comprises the following steps:
[0008] (1) coating a layer of gold atoms on the surface of the TiO2 nano-microspheres to obtain TiO2 nano-microspheres coated with the gold atoms;
[0009] (2) adding HAuCl4 aqueous solution, sodium hexadecylbenzenesulfonate (CTAB) aqueous solution, sodium ascorbate (AA) aqueous solution into water, and adding TiO2 nanospheres coated with a gold atomic layer to react, growing a gold shell on the gold atomic layer, and obtaining a TiO2@Au Jauns core-half-shell structure nanomaterial;
[0010] (3) adding ε-polylysine and 3-isocyanatepropyltrimethoxysilane to dimethyl sulfoxide, heating for reaction, dialyzing, and freeze-drying to obtain trimethoxysilane-functionalized ε-polylysine;
[0011] (4) Adding trimethoxysilane-functionalized ε-polylysine and TiO2@Au Jauns core-semi-shell structured nanomaterials into water, stirring the reaction, and obtaining ε-polylysine-modified TiO2@Au Jauns core-semi-shell structured nanomaterials.
[0012] Furthermore, the preparation method of TiO2 nanospheres in step (1) comprises the following steps:
[0013] In ethanol solution, isopropyl titanate (TTIP) was used as a precursor, hexadecylamine (HDA) was used as a structure directing agent, and KCl was used as an ion regulator to promote the formation of spherical TiO2 particles and obtain TiO2 nanospheres.
[0014] Furthermore, the volume ratio of water to ethanol in the ethanol solution is 1:0.2-2.
[0015] Furthermore, the molar ratio of HDA, ethanol solution, KCl, and TTIP is (0.3-0.6): (2-5): (4.5×10 -3~ 6.5×10 -3 ):(0.5~1.5).
[0016] Furthermore, in step (1), an ion sputtering device is used to plate a layer of gold atoms on the surface of the TiO2 nanospheres. The setting parameters of the ion sputtering device are: sputtering current is 5 to 10 mA, sputtering time is 30 to 180 s, and the thickness of the gold atomic layer is 1 to 5 gold atoms.
[0017] Furthermore, in step (2), the concentration of the HAuCl4 aqueous solution is 0.005 to 0.5 mol / L.
[0018] Furthermore, in step (2), the concentration of the sodium hexadecylbenzenesulfonate (CTAB) aqueous solution is 0.1 to 0.5 mol / L.
[0019] Furthermore, in step (2), the concentration of the sodium ascorbate (AA) aqueous solution is 0.05 to 0.4 mol / L.
[0020] Furthermore, in step (2), the volume ratio of water, HAuCl4 aqueous solution, sodium hexadecylbenzenesulfonate (CTAB) aqueous solution, and sodium ascorbate (AA) aqueous solution is 3: (0.1-1): (1-10): (0.01-0.1).
[0021] Furthermore, in step (2), the reaction temperature is 0 to 50° C., and the reaction time is 5 to 50 h.
[0022] Furthermore, in step (2), the mass of TiO2 nanospheres coated with a gold atomic layer added to every 10 mL of water is 1 to 20 mg.
[0023] Furthermore, in step (3), the molar volume ratio of ε-polylysine, 3-isocyanatepropyltrimethoxysilane and dimethyl sulfoxide is 0.1:(0.02-0.1):(50-100) mol / mol / mL.
[0024] Furthermore, in step (3), the temperature of the heating reaction is 10 to 80° C., and the time of the heating reaction is 6 to 48 hours.
[0025] Furthermore, in step (4), the mass ratio of trimethoxysilane functionalized ε-polylysine to the Jauns core-half shell structure of TiO2@Au is 1:(10-50).
[0026] Furthermore, in step (4), the stirring reaction time is 1 to 18 hours.
[0027] The invention discloses an antibacterial application of the ε-polylysine modified TiO2@Au Jauns core-half shell structure nanomaterial.
[0028] Furthermore, the antibacterial process requires ultrasonic treatment.
[0029] Furthermore, the bacteria are prokaryotic bacteria such as Escherichia coli and Staphylococcus aureus.
[0030] The antibacterial principle of the nanomaterial of the Jauns core-half shell structure of the ε-polylysine-modified TiO2@Au of the present invention is as follows:
[0031] As shown in Figure 1: the ε-polylysine on the surface of the nanoparticles of the Jauns core-half-shell structure of TiO2@Au enables the nanoparticles to actively target the bacterial cell membrane. In the ultrasonic field, the TiO2 nanospheres form electron-hole pairs under the action of ultrasound, and Au can inhibit the recombination of electron-hole pairs by accepting electrons, resulting in further separation of electron-hole pairs. Therefore, the hole enrichment on the side of the TiO2 nanospheres can destroy the electron transport chain on the bacterial cell membrane, and produce reactive oxygen species (ROS) with antibacterial properties in the bacterial cells, which plays an antibacterial role; after the ε-polylysine is targeted and embedded in the bacterial cell membrane, the electrons in the normal aerobic respiration electron transport chain on the bacterial cell membrane (black dotted line in the figure) are pulled into the TiO2 nanospheres (red dotted line in the figure), thereby destroying the redox balance inside the bacteria, causing the O2 that should have been reduced to H2O in the bacteria to be oxidized to generate ROS with antibacterial effects; the electron enrichment on the Au half-shell side can reduce the H in the bacterial microenvironment. + , H 2 O 2 Generate H2, O2, or reduce H2O2 produced by bacteria to generate O2. After the bubbles separate from the nanoparticles, they can form thrust to further destroy the bacterial cell membrane and even the biofilm generated by bacteria.
[0032] In summary, the present invention is to wrap the upper half of the gold shell on the outer shell of TiO2 nanospheres to increase the yield of reactive oxygen species (ROS) released in the body. At the same time, the gold shell side of the Jauns core-half shell structure of TiO2@Au has a reducing property due to electron accumulation, which can reduce H in the bacterial microenvironment. + And hydrogen peroxide produces other, further destroy the bacterial cell membrane, thus playing a better antibacterial effect.
[0033] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0034] The nanomaterial of the Jauns core-half-shell structure of the ε-polylysine modified TiO2@Au proposed in the present invention has good antibacterial properties, and its advantages are reflected in: 1) the Jauns core-half-shell structure separates the oxidation end from the reduction end, realizing the unity of structure and function; 2) the TiO2@Au does not directly oxidize O2 to produce ROS, but induces the disorder of the aerobic respiration electron chain to produce ROS, and the required ultrasonic power is lower; 3) ROS is directly produced in bacterial cells, overcoming the problems of extremely short half-life and difficulty in penetrating membranes of ROS, and improving the antibacterial efficiency; 4) Ultrasound is used to stimulate the production of ROS, overcoming the problem of insufficient penetration of light in the body in traditional photodynamic therapy; 5) the Jauns core-half-shell structure of TiO2@Au has the function of a nanomotor, that is, it can move toward one side of TiO2 under the action of ultrasound, which can assist ROS in achieving a better antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The antibacterial principle diagram of the nanomaterial of the Jauns core-half shell structure of the ε-polylysine-modified TiO2@Au of the present invention;
[0036] Figure 2 Transmission electron microscopy (TEM) and elemental analysis of the Jauns core-half-shell structured nanomaterial of ε-polylysine modified TiO2@Au prepared in Example 1;
[0037] Figure 3 It is a diagram demonstrating the singlet oxygen (ROS) yield of the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial and TiO2 nanospheres prepared in Example 1 under different ultrasonic time;
[0038] Figure 4 The antibacterial effect diagram of the Jauns core-half-shell structure nanomaterial of ε-polylysine modified TiO2@Au prepared in Example 1 and the nanoparticles prepared in Comparative Examples 1, 2, and 3;
[0039] Figure 5 This is a diagram demonstrating that the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial in Example 6 destroys the electron transport chain of bacterial aerobic respiration under ultrasound. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0041] Example 1
[0042] 1) Preparation of TiO2 nanospheres: 2.4 g HDA was dissolved in 300 mL ethanol solution, and then 1.08 g KCl solution (0.1 mol / L) was added, followed by mechanical stirring for 10 min, and then 5.68 g TTIP was added at 37°C. After the addition was completed, the mixture was allowed to stand and washed by centrifugation several times with anhydrous ethanol to obtain a TiO2 nanosphere solution.
[0043] 2) Dissolve the TiO2 nanospheres in 40 ml of anhydrous ethanol solution, drop them onto a silicon plate, dry them naturally, and then place the silicon plate with the TiO2 nanosphere solution on an ion sputtering instrument. The parameters of the ion sputtering instrument are: sputtering current is 10 mA, and sputtering time is 60 seconds. A layer of gold atoms is plated on about half of the surface of the TiO2 nanospheres. The thickness of the gold atoms is 1 gold atom. After separation and drying, the TiO2 nanospheres plated with the gold atoms are ready for use.
[0044] 3) Add 5 mL of 0.01 mol / L HAuCl4 aqueous solution, 30 mL of 0.2 mol / L sodium hexadecylbenzenesulfonate (CTAB) aqueous solution, 0.5 mL of 0.1 mol / L sodium ascorbate (AA) aqueous solution, and 15 mg of TiO2 nanospheres coated with a gold atomic layer to 30 mL of deionized water, react at 35 ° C for 12 h, grow a gold shell on the gold atomic layer, and obtain a TiO2@Au Jauns core-half shell structure nanomaterial;
[0045] 4) Add 0.1 mol ε-polylysine and 0.05 mol 3-isocyanatepropyltrimethoxysilane to 50 mL dimethyl sulfoxide, react at 20°C for 12 h, dialyze and freeze-dry to obtain trimethoxysilane-functionalized ε-polylysine; add 5 mg trimethoxysilane-functionalized ε-polylysine and 100 mg TiO2@Au Jauns core-semi-shell structured nanomaterials to water and stir to react for 10 h to obtain ε-polylysine-modified TiO2@Au Jauns core-semi-shell structured nanomaterials (abbreviated as: TiO2@Au nanoparticles).
[0046] The prepared ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial was characterized by TEM, and its morphology was observed and elemental analysis was performed. The results are as follows: Figure 1 shown.
[0047] Figure 2 The transmission electron microscopy (TEM) and elemental analysis diagram of the Jauns core-semi-shell structure nanomaterial of TiO2@Au modified with ε-polylysine prepared in Example 2, wherein A is the TEM diagram, B is the Ti element distribution diagram, C is the Au element distribution diagram, and D is the O element distribution diagram. Figure 2It can be seen that the particle size of the ε-polylysine modified TiO2@Au Jauns core-half shell structure nanoparticles is about 400nm, which is a core-half shell structure. Through elemental analysis of the core and shell components, it can be found that the main elements in the spherical core are Ti and O, so it can be inferred to be TiO2; the main element in the half shell is Au, and one layer can be inferred to be a half-gold shell structure. Therefore, it can be determined that the nanoparticles are a Jauns core-half shell structure of TiO2 core-Au half shell.
[0048] Comparative Example 1
[0049] The experimental process is the same as in the example, except that the TiO2 microspheres are prepared according to the conditions of Example 1, and no gold plating and subsequent treatment are performed, for comparison:
[0050] 2.4 g HDA was dissolved in 300 mL ethanol solution, and then 1.08 g KCl solution (0.1 mol / L) was added, followed by mechanical stirring for 10 min, and then 5.68 g TTIP was added at 37°C. After the addition was completed, the mixture was kept still and washed by centrifugation with anhydrous ethanol several times to obtain a TiO2 nanosphere solution.
[0051] Comparative Example 1
[0052] The experimental process is the same as in the example, except that the TiO2@Au Jauns core-half-shell structure nanomaterial is prepared according to the conditions of Example 1, and ε-polylysine modification is no longer performed, as a comparison:
[0053] 1) Preparation of TiO2 nanospheres: 2.4 g HDA was dissolved in 300 mL ethanol solution, and then 1.08 g KCl solution (0.1 mol / L) was added, followed by mechanical stirring for 10 min, and then 5.68 g TTIP was added at 37°C. After the addition was completed, the mixture was allowed to stand and washed by centrifugation several times with anhydrous ethanol to obtain a TiO2 nanosphere solution.
[0054] 2): Dissolve the TiO2 nanospheres in 40 ml of anhydrous ethanol solution, drop them onto a silicon plate, dry them naturally, and then place the silicon plate with the TiO2 nanosphere solution on an ion sputtering instrument. The parameters of the ion sputtering instrument are: sputtering current is 10 mA, and sputtering time is 60 seconds. A single-atom gold layer is plated on about half of the surface of the TiO2 nanospheres. The thickness of the single-atom gold layer is 1 gold atom. After separation and drying, the TiO2 nanospheres plated with the single-atom gold layer are ready for use.
[0055] 3) Add 5 mL of 0.01 mol / L HAuCl4 aqueous solution, 30 mL of 0.2 mol / L sodium hexadecylbenzenesulfonate (CTAB) aqueous solution, 0.5 mL of 0.1 mol / L sodium ascorbate (AA) aqueous solution to 30 mL of deionized water, and add TiO2 nanospheres coated with a single atomic gold layer, react at 35°C for 12 h, grow a gold shell on the single atomic gold layer, and obtain a TiO2@Au Jauns core-half shell structure nanomaterial (abbreviated as: TiO2@Au nanoparticles without ε-polylysine modification);
[0056] Comparative Example 3
[0057] The experimental process is the same as in the example, except that the TiO2@Au nanoparticles are prepared according to the conditions of Example 1, and the TiO2 is not plated with a gold atomic layer by ion sputtering, as a comparison:
[0058] 1) Preparation of TiO2 nanospheres: 2.4 g HDA was dissolved in 300 mL ethanol solution, and then 1.08 g KCl solution (0.1 mol / L) was added, followed by mechanical stirring for 10 min, and then 5.68 g TTIP was added at 37°C. After the addition was completed, the mixture was allowed to stand and washed by centrifugation several times with anhydrous ethanol to obtain a TiO2 nanosphere solution.
[0059] 2) Add 5 mL of 0.01 mol / L HAuCl4 aqueous solution, 30 mL of 0.2 mol / L sodium hexadecylbenzenesulfonate (CTAB) aqueous solution, 0.5 mL of 0.1 mol / L sodium ascorbate (AA) aqueous solution, and 15 mg of TiO2 nanospheres to 30 mL of deionized water, and react at 35 °C for 12 h to obtain a TiO2@Au nanomaterial as a control;
[0060] 3) Add 0.1 mol ε-polylysine and 0.05 mol 3-isocyanatepropyltrimethoxysilane into 50 mL dimethyl sulfoxide, react at 20°C for 12 h, dialyze and freeze-dry to obtain trimethoxysilane-functionalized ε-polylysine; add 5 mg trimethoxysilane-functionalized ε-polylysine and 100 mg TiO2@Au Jauns core-shell structure nanomaterial into water and stir for 10 h to obtain ε-polylysine-modified TiO2@Au nanomaterial (abbreviated as: TiO2@Au nanoparticles without gold coating) as a control.
[0061] Example 2
[0062] The preparation process is the same as in Example 1, specifically as follows:
[0063] 1) Preparation of TiO2 nanospheres: 3.5 g HDA was dissolved in 300 mL ethanol solution, and then 1.08 g KCl solution (0.1 mol / L) was added, followed by mechanical stirring for 10 min, and then 7.2 g TTIP was added at 37°C. After the addition was completed, the mixture was allowed to stand and washed by centrifugation with anhydrous ethanol several times to obtain a TiO2 nanosphere solution.
[0064] 2) Dissolve the TiO2 nanospheres in 40 ml of anhydrous ethanol solution, drop them onto a silicon plate, dry them naturally, and then place the silicon plate with the TiO2 nanosphere solution on an ion sputtering instrument. The parameters of the ion sputtering instrument are: sputtering current of 5 mA, sputtering time of 180 s, and plate a layer of gold atoms on about half of the surface of the TiO2 nanospheres. The thickness of the gold atomic layer is 5 gold atoms. After separation and drying, the TiO2 nanospheres plated with the gold atomic layer are ready for use.
[0065] 3) Add 7 mL of 0.01 mol / L HAuCl4 aqueous solution, 50 mL of 0.2 mol / L sodium hexadecylbenzenesulfonate (CTAB) aqueous solution, 0.4 mL of 0.1 mol / L sodium ascorbate (AA) aqueous solution to 30 mL of deionized water, and add TiO2 nanospheres coated with a gold atomic layer, react at 35 ° C for 20 h, grow a gold shell on the gold atomic layer, and obtain a TiO2@Au Jauns core-half shell structure nanomaterial;
[0066] 4) Add 0.1 mol ε-polylysine and 0.07 mol 3-isocyanatepropyltrimethoxysilane to 50 mL dimethyl sulfoxide, react at 60°C for 12 h, dialyze and freeze-dry to obtain trimethoxysilane-functionalized ε-polylysine; add 5 mg trimethoxysilane-functionalized ε-polylysine and 200 mg TiO2@Au Jauns core-semi-shell structured nanomaterials to water and stir for 10 h to obtain ε-polylysine-modified TiO2@Au Jauns core-semi-shell structured nanomaterials.
[0067] Example 3
[0068] The preparation process is the same as in Example 1, specifically as follows:
[0069] 1) Preparation of TiO2 nanospheres: 2.4 g HDA was dissolved in 300 mL ethanol solution, and then 1.08 g KCl solution (0.1 mol / L) was added, followed by mechanical stirring for 10 min, and then 6.5 g TTIP was added at 37°C. After the addition was completed, the mixture was allowed to stand and washed by centrifugation with anhydrous ethanol for multiple times to obtain a TiO2 nanosphere solution.
[0070] 2) Dissolve the TiO2 nanospheres in 40 ml of anhydrous ethanol solution, drop them onto a silicon plate, dry them naturally, and then place the silicon plate with the TiO2 nanosphere solution on an ion sputtering instrument. The parameters of the ion sputtering instrument are: sputtering current of 10 mA, sputtering time of 120 s, and plate a layer of gold atoms on about half of the surface of the TiO2 nanospheres. The thickness of the gold atomic layer is 3 gold atoms. After separation and drying, the TiO2 nanospheres plated with the gold atomic layer are ready for use.
[0071] 3) Add 7 mL of 0.01 mol / L HAuCl4 aqueous solution, 40 mL of 0.2 mol / L sodium hexadecylbenzenesulfonate (CTAB) aqueous solution, 0.5 mL of 0.1 mol / L sodium ascorbate (AA) aqueous solution to 30 mL of deionized water, and add TiO2 nanospheres coated with a gold atomic layer, react at 60°C for 12 h, grow a gold shell on the gold atomic layer, and obtain a TiO2@Au Jauns core-half-shell structure nanomaterial;
[0072] 4) Add 0.1 mol ε-polylysine and 0.02 mol 3-isocyanatepropyltrimethoxysilane to 50 mL dimethyl sulfoxide, react at 60°C for 12 h, dialyze and freeze-dry to obtain trimethoxysilane-functionalized ε-polylysine; add 5 mg trimethoxysilane-functionalized ε-polylysine and 50 mg TiO2@Au Jauns core-semi-shell structured nanomaterials to water and stir for 10 h to obtain ε-polylysine-modified TiO2@Au Jauns core-semi-shell structured nanomaterials.
[0073] Example 4 Performance Test
[0074] 20 mg of the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structured nanomaterial (TiO2@Au nanoparticles) prepared in Example 1 and the TiO2 nanospheres (TiO2 microspheres) prepared in the first step of Example 1 were dissolved in 5 ml of deionized water, and 100 mg of 1,3-diphenylisobenzofuran (a fluorescent dye that can be oxidized by ROS and fluorescence quenched) was added. The mixture was ultrasonicated in an ultrasonic machine for 1 min, 2 min, 5 min, 10 min, 20 min, and 30 min, respectively. A 100 ul pipette was used to draw the ultrasonicated solution and drop it into a 96-well plate. The 96-well plate was placed in a microplate spectrophotometer for absorbance detection. The results are as follows: Figure 3 shown.
[0075] Figure 3 The singlet oxygen (ROS) yield of the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial and TiO2 microspheres prepared in Example 1 under different ultrasonic time is demonstrated. Figure 3It can be seen that the main absorption peak of 1,3-diphenylisobenzofuran is at 455nm. Under ultrasound, the absorption peaks of the solution of Jauns core-semi-shell structure nanomaterials and TiO2 microspheres with the addition of ε-polylysine modified TiO2@Au both show a downward trend, indicating that ROS are generated. However, by comparison, it can be found that the downward trend of the absorption peak of the solution of Jauns core-semi-shell structure nanomaterials with the addition of ε-polylysine modified TiO2@Au is more obvious than that of the solution of TiO2 microspheres, indicating that more ROS are generated in the solution of Jauns core-semi-shell structure nanomaterials with ε-polylysine modified TiO2@Au. Therefore, it can be explained that TiO2@Au nanoparticles can generate ROS under ultrasound, and because the semi-gold shell inhibits the recombination of electron-hole pairs, its efficiency in generating ROS is higher than that of TiO2 microspheres.
[0076] Example 5 Antibacterial Performance Analysis
[0077] Take 6mL of Gram-negative bacteria-Escherichia coli (Nanjing Lezhen Biotechnology Co., Ltd.) stock solution, the bacterial concentration is 10 5 / mL, divided into 10 parts, and treated as follows: Figure 4 0.5 mg of the materials prepared in Example 1 and Comparative Examples 1-3 were added, and ultrasonic treatment or no ultrasonic treatment was performed. The frequency, power and time of the ultrasound were 1 MHz, 0.5 W / cm 2 , 10 minutes. Then put it in a 37℃ constant temperature shaker for 1 hour. Then take 40μL of the above-treated bacterial solution and drop it into LB agar medium. After culturing for 24 hours, observe the colony. The results are as follows Figure 4 shown.
[0078] Figure 4 The antibacterial effect diagram of the Jauns core-semi-shell structure nanomaterial of ε-polylysine modified TiO2@Au prepared in Example 1 and the nanoparticles prepared in Comparative Examples 1, 2, and 3 is shown in FIG. Figure 4It can be found that the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial prepared in Example 1 in Group 5)b has a very good antibacterial effect under an ultrasonic field. By comparing 1)a and 1)b, it can be found that ultrasound itself does not have a bactericidal effect, which can explain that the antibacterial effect of 5)b is exerted by TiO2@Au nanoparticles under the action of ultrasound. By comparing 2)b, 3)b and 5)b, the antibacterial effect of the samples prepared in Comparative Examples 1 and 2 under low-power ultrasound is very weak, indicating that the preparation of the complete ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial is the basis for the TiO2@Au nanoparticles to play a role, and also verifies the antibacterial mechanism of the TiO2@Au nanoparticles described in the specification from the side. By comparing 4)b and 5)b, it can be found that in the preparation of Comparative Example 3, ion sputtering was not performed to plate a layer of gold atoms on TiO2. Although subsequent culturing and modification with ε-polylysine in gold shell growth solution were tried, the product showed almost no antibacterial effect, indicating that the lack of ion sputtering to plate a layer of gold atoms on TiO2 made it impossible for the sample prepared in Comparative Example 3 to form the Jauns core-half shell structure of TiO2@Au. Therefore, the preparation scheme described in the present invention is a necessary condition for constructing the Jauns core-half shell structure of TiO2@Au.
[0079] Example 7 Analysis of the antibacterial mechanism of TiO2@Au nanoparticles
[0080] 0.2 mg of the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial prepared in Example 1 was mixed with 2 mL of Gram-negative bacteria-Escherichia coli (Nanjing Lezhen Biotechnology Co., Ltd.) stock solution, with a bacterial concentration of 10 5 / mL, and co-cultured on a 37℃ constant temperature shaker for 1h. Then the culture solution containing the nanoparticles and bacteria was spin-coated on a 20mm×20mm indium tin oxide (ITO) conductive glass, and dried to form a working electrode film (experimental group). Linear sweep voltammetry (LSV) was used to measure the open circuit voltage in the voltage range of -0.3 to 0.3V without ultrasound (denoted as: bacteria + TiO2@Au nanoparticles) and ultrasound (denoted as: bacteria + TiO2@Au nanoparticles + ultrasound). The results are as follows Figure 5 The same method was used to compare the effects of ultrasound on Escherichia coli alone (referred to as bacteria + ultrasound) and TiO2@Au Jauns core-semishell structure nanomaterials modified with ε-polylysine alone (referred to as TiO2@Au nanoparticles + ultrasound). The results are shown in Figure 2. Figure 5 shown.
[0081] Figure 5This is a diagram showing that the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial destroys the electron transport chain of bacterial aerobic respiration under ultrasound in Example 6. Figure 5 It can be seen that compared with the unultrasonicated ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial (bacteria + TiO2@Au nanoparticles), the co-cultured E. coli group (bacteria + TiO2@Au nanoparticles + ultrasound) has a significant change in current after ultrasound, indicating that the ultrasound process generates electrons. In order to exclude the influence of other factors, the same amount of E. coli and ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterials were coated on conductive glass to prepare working electrodes, and the current after ultrasound was measured. It can be found that the changes in the E. coli group (bacteria + ultrasound) and the TiO2@Au nanoparticle group (TiO2@Au nanoparticles + ultrasound) are much smaller than those in the experimental group. Therefore, it can be considered that the ε-polylysine-modified TiO2@Au Jauns core-semi-shell structure nanomaterial destroys the aerobic respiration electron transport chain of bacteria and pulls out electrons.
Claims
1. A Jauns core-half-shell structure nanomaterial of TiO2@Au modified with ε-polylysine, characterized in that: The ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial is a TiO2 nano-microsphere core coated with a gold atomic layer and a half-gold shell is grown on the outer side of the core, which is modified with ε-polylysine.
2. A method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 1, characterized in that: The following steps are involved: (1) coating a layer of gold atoms on the surface of the TiO2 nano-microspheres to obtain TiO2 nano-microspheres coated with the gold atoms; (2) adding HAuCl4 aqueous solution, sodium hexadecylbenzenesulfonate aqueous solution, sodium ascorbate aqueous solution to water, and adding TiO2 nanospheres coated with a gold atomic layer to react, growing a gold shell on the gold atomic layer, and obtaining a TiO2@Au Jauns core-half-shell structure nanomaterial; (3) adding ε-polylysine and 3-isocyanatepropyltrimethoxysilane to dimethyl sulfoxide, heating for reaction, dialyzing, and freeze-drying to obtain trimethoxysilane-functionalized ε-polylysine; (4) Adding trimethoxysilane-functionalized ε-polylysine and TiO2@Au Jauns core-semi-shell structured nanomaterials into water, stirring the reaction, and obtaining ε-polylysine-modified TiO2@Au Jauns core-semi-shell structured nanomaterials.
3. The method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 2, characterized in that: In step (1), a layer of gold atoms is plated on the surface of the TiO2 nanospheres by using an ion sputtering instrument. The setting parameters of the ion sputtering instrument are: sputtering current is 5 to 10 mA, sputtering time is 30 to 180 s, and the thickness of the gold atomic layer is 1 to 5 gold atoms.
4. The method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 2, characterized in that: In step (2), the concentration of the HAuCl4 aqueous solution is 0.005-0.05 mol / L, the concentration of the sodium hexadecylbenzenesulfonate aqueous solution is 0.1-0.5 mol / L, and the concentration of the sodium ascorbate aqueous solution is 0.05-0.4 mol / L; the volume ratio of water, HAuCl4 aqueous solution, sodium hexadecylbenzenesulfonate aqueous solution, and sodium ascorbate aqueous solution is 3:(0.1-1):(1-10):(0.01-0.1).
5. The method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 2, characterized in that: In step (2), the reaction temperature is 0-50° C., the reaction time is 5-50 h, and the mass of the TiO2 nanospheres coated with the gold atomic layer added to every 10 mL of water is 1-20 mg.
6. The method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 2, characterized in that: In step (3), the molar volume ratio of ε-polylysine, 3-isocyanatepropyltrimethoxysilane and dimethyl sulfoxide is 0.1:(0.02-0.1):(50-100) mol / mol / mL.
7. The method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 2, characterized in that: In step (3), the heating reaction temperature is 10 to 80° C., and the heating reaction time is 6 to 48 hours.
8. The method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 2, characterized in that: In step (4), the mass ratio of trimethoxysilane functionalized ε-polylysine to the Jauns core-half shell structure of TiO2@Au is 1:(10-50).
9. The method for preparing the ε-polylysine-modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 2, characterized in that: In step (4), the stirring reaction time is 1 to 18 hours.
10. Use of the ε-polylysine modified TiO2@Au Jauns core-half-shell structure nanomaterial according to claim 1 in antibacterial applications.